Exploring the use of sticker in male WhatsApp group - Mohammed Rezewan, Mohammed Zahin; Razali, Khairil Azwar (Kulliyyah of Languages and Management, 2021)
This research's main objectives are to explore the use of WhatsApp Sticker in male-only WhatsApp groups with the intention to find the most used WhatsApp Sticker theme and the situation where the most Sticker theme occurs. The data was collected from Mahallah Zaid Harithah (MZH), B6 WhatsApp group called the ‘Gua’ and was analysed using a content analysis method. There are a total of 93 Stickers identified and the collected data were assigned to a specific theme based on the previous comment before. Based on the findings, it is shown that Silly Sticker is the most used sticker, and the sticker occurs in situations where someone is reacting to a certain statement, comment, message, or information and in a joking situation. It is also found that each Sticker theme can be used in various situations despite having its own assigned theme. As for future research, it is highly recommended that a bigger sample should be considered to ensure the data collection will be ampler and more outcomes can be drawn in the field of stickers in the WhatsApp group study.